1989
DOI: 10.1002/mus.880121109
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical differential distribution of S‐100α and S‐100β in the peripheral nervous system of the rat

Abstract: The localization of the alpha subunit of the S-100 protein (S-100 alpha) and beta subunit (S-100 beta) was studied in the peripheral nervous system of the rat. In peripheral nerves, S-100 alpha and S-100 beta were found in the cytoplasm of Schwann cells. Axons were positively stained in part by S-100 alpha and almost totally by S-100 beta. In the dorsal root ganglia, S-100 alpha was found in satellite cells and their processes and in some neurons. S-100 beta was found in more of the large neurons, but almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
3
20
0
4
Order By: Relevance
“…According to Vega et al (7), not all SGC are positive for vimentin; however, we found positive immunoreactivity in the entire population of SGC regardless of the type or size of the neuron. Observation of this reaction by confocal microscopy revealed that the expression of vimentin is more evident near the membrane, which is interesting because it is known that vimentin is a protein that participates in the communication between the cell surface and the nucleus (16). In view of these considerations, our results suggest that vimentin may exert its function through interaction with actin microfilaments, which are typically located under the cytoplasmic membrane.…”
supporting
confidence: 57%
“…According to Vega et al (7), not all SGC are positive for vimentin; however, we found positive immunoreactivity in the entire population of SGC regardless of the type or size of the neuron. Observation of this reaction by confocal microscopy revealed that the expression of vimentin is more evident near the membrane, which is interesting because it is known that vimentin is a protein that participates in the communication between the cell surface and the nucleus (16). In view of these considerations, our results suggest that vimentin may exert its function through interaction with actin microfilaments, which are typically located under the cytoplasmic membrane.…”
supporting
confidence: 57%
“…The present results suggest that S100 protein of sensory corpuscles consists of S100␣ and S100␤ proteins, as it was demonstrated for glial cells of the peripheral nervous system (Sugimura et al, 1989). The homo-or heterodimeric combination of S100␣ and S100␤ proteins predominate in the mammalian peripheral nervous system (for references see Schä fer and Heizmann, 1996).…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the central axons of cutaneous sensory corpuscles, at least in man, lack S100 proteins. Consequently, it must be assumed that sensory neurons containing S100 (Vega et al, 1989;Ichikawa et al, 1997), S100␣ (Isobe et al, 1984;Sugimura et al, 1989;Vega et al, 1989Vega et al, , 1991, and S100␤ (Sugimura et al, 1989;Vega et al, 1991;Yang et al, 1995) proteins do not project to the skin, do not exist in adult men, and do not form cutaneous sensory corpuscles (for references see Vega et al, 1996), or they lack this antigen just in that localization. Recently we observed that neuronal S100 proteins in dorsal root ganglion sensory neurons occur only in the rat and not in other mammals, including man (Albuerne et al, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No Sistema Nervoso Periférico SNP foi encontrada S100β em células de Schwann, sugerindo envolvimento na produção de mielina, e manutenção da meninge pia mater. (Sugimura et al, 1989;Mata et al, 1990).…”
Section: Discussionunclassified